Clinical Medical Ethics : Landmark Works of Mark Siegler, MD - Roberts, Laura Weiss; Siegler, Mark (Springer International Publishing : Imprint: Springer, 2017)
This instant gold standard title is a major contribution to the field of clinical medical ethics and will be used widely for reference and teaching purposes for years to come. Throughout his career, Mark Siegler, MD, has written on topics ranging from the teaching of clinical medical ethics to end-of-life decision-making and the ethics of advances in technology. With more than 200 journal publications and 60 book chapters published in this area over the course of his illustrious career, Dr. Siegler has become the pre-eminent scholar and teacher in the field. Indeed his work has had a profound impact on a range of therapeutic areas, especially internal medicine, pediatrics, surgery, oncology, and medical education. Having grown steadily in importance the last 30 years, clinical ethics examines the practical, everyday ethical issues that arise in encounters among patients, doctors, nurses, allied health workers, and health care institutions. The goal of clinical ethics is to improve patient care and patient outcomes, and almost every large hospital now has an ethics committee or ethics consultation service to help resolve clinical ethical problems; and almost every medical organization now has an ethics committee and code of ethics. Most significantly, clinical ethics discussions have become a part of the routine clinical discourse that occurs in outpatient and inpatient clinical settings across the country. This seminal collection of 46 landmark works written by Dr. Siegler with colleagues throughout his career was edited by Dr. Laura Weiss Roberts and by Dr. Siegler. Dr. Roberts is a prominent psychiatric ethicist and physician-scientist as well as a mentee and longtime collaborator of Dr. Siegler. The text is organized around five themes of foundational scholarship: restoring and transforming the ethical basis of modern clinical medicine, the doctor-patient relationship, education and professionalism, end-of-life care, and clinical innovation.With introductory perspectives by a group of renowned scholars in medicine, Clinical Medical Ethics: Landmark Works of Mark Siegler, MD explains the field authoritatively and comprehensively and will be of invaluable assistance to all clinicians and scholars concerned with clinical ethics. .
Keywords: Medicine.; Internal medicine.; Cardiology.; Endocrinology.; Neurology.; elektronické knihy; electronic books